Indexing databases on Malay world studies: The critical role of knowledge workers - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2004)
The construction of databases and the designing search engines and interfaces are no longer the monopoly of major online services or database publishers. Harnessing the power of such technology, ATMA has been constructing in-house databases on Malay world studies since April 1999, following the example of major online databases in offering scholars and researchers a collection of materials that can meet their needs. We now have three fully functioning databases, namely Single Articles on Malay World Studies, Malay Proverbs and Pantun, Syair and Dondang Sayang of Malaysian Baba. All of them are accessible at http://www.atma.ukm.my. Now, scholars of the Malay World from all over the world are able to enjoy customised information and document retrieval for the first time. With the search process being increasingly carried out by the end-users themselves, the efficiency, precision and relevance of search results become a major question. Simplicity and quality become necessary to a database’s survival. However, online searches can stumble on the simplest of obstacles: the connection suddenly breaks, the log-in procedure changed, the password invalid, the search statement too long, the manual does not give the help one needs, or the lack of certain search fields leaves users helpless, etc. These problems accumulate and complicate matters when several online systems are accessed simultaneously. Since errors can occur at each stage in database building, thus, dedication, care, institutional support and many other critical factors are vital if information workers are to perform well, and if they are to deliver services satisfactorily